Comparative analyses of industrial‐scale human platelet lysate preparations. Issue 12 (8th October 2017) - Pierce, Jan; Benedetti, Eric; Preslar, Amber; Jacobson, Pam; Jin, Ping; Stroncek, David F.; Reems, Jo‐Anna
Abstract : BACKGROUND: Efforts are underway to eliminate fetal bovine serum from mammalian cell cultures for clinical use. An emerging, viable replacement option for fetal bovine serum is human platelet lysate (PL) as either a plasma‐based or serum‐based product. STUDY DESIGN AND METHODS: Nine industrial‐scale, serum‐based PL manufacturing runs (i.e., lots) were performed, consisting of an average ± standard deviation volume of 24.6 ± 2.2 liters of pooled, platelet‐rich plasma units that were obtained from apheresis donors. Manufactured lots were compared by evaluating various biochemical and functional test results. Comprehensive cytokine profiles of PL lots and product stability tests were performed. Global gene expression profiles of mesenchymal stromal cells (MSCs) cultured with plasma‐based or serum‐based PL were compared to MSCs cultured with fetal bovine serum. RESULTS: Electrolyte and protein levels were relatively consistent among all serum‐based PL lots, with only slight variations in glucose and calcium levels. All nine lots were as good as or better than fetal bovine serum in expanding MSCs. Serum‐based PL stored at −80°C remained stable over 2 years. Quantitative cytokine arrays showed similarities as well as dissimilarities in the proteins present in serum‐based PL. Greater differences in MSC gene expression profiles were attributable to the starting cell source rather than with the use of either PL or fetal bovine serum as a culture supplement. CONCLUSION: Using a large‐scale, standardized method, lot‐to‐lot variations were noted for industrial‐scale preparations of serum‐based PL products. However, all lots performed as well as or better than fetal bovine serum in supporting MSC growth. Together, these data indicate that off‐the‐shelf PL is a feasible substitute for fetal bovine serum in MSC cultures.